Reconstruction of the Narrative of the Elderly Regarding the Modernization of Islamic Education in Minangkabau in the 20th Century - Yudi Gucandra; Iswantir M; Arif Rahmat Triasa; Ade Putra Hayat; Budi Harto (Tarikhuna: Journal of History and History Education, 2025)
This study reconstructs the narrative of the elders regarding the modernization of Islamic education in Minangkabau in the early 20th century by revisiting the perception that labels them as a conservative and anti-change group. Using an anthropological-interpretive approach and a literature review, this study traces the social, cultural, and epistemological dialectics between the elders and the youth in the transformation of Islamic education from the traditional surau to the modern madrasah. The results of the analysis show that the elders' resistance was selective and rational, not ideological. They implemented adaptive strategies based on local wisdom through the principle of adat basandi syarak, syarak basandi Kitabullah (custom based on sharia, sharia based on the Holy Book), which served as a mechanism for filtering values against the influence of Western modernity and Middle Eastern purification. Traditional suraus served as social laboratories where innovations were tested before being institutionalized, while institutions such as Sumatera Thawalib became evidence of creative negotiations between young innovators and the architects of tradition. This study also emphasizes the relevance of ethnopedagogy and the participation of elders in contemporary Islamic education policy to maintain a balance between transformation and the preservation of values. Thus, the modernization of Islamic education in Minangkabau is the result of a dialectical synergy that combines modern rationality and local spirituality as the basis for the birth of Islamic moderation in the archipelago.